2014
DOI: 10.1016/j.smrv.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems and work injuries: A systematic review and meta-analysis

Abstract: This systematic review confirmed the association between sleep problems and work injuries and, for the first time, quantified its magnitude. As sleep problems are of growing concern in the population, these findings are of interest for both sleep researchers and occupational physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
208
5
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 336 publications
(226 citation statements)
references
References 63 publications
9
208
5
4
Order By: Relevance
“…Shift work disorder is characterized by certain clinically significant disturbances in sleep, fatigue, and/or circadian alignment in shift workers that cannot be attributed to other causes (69). In addition, excessive daytime sleepiness due to shift work, sleep deprivation, sleep disorders, or combinations of these factors is associated with an increased risk of work-related injuries (70)(71)(72)(73). In particular, inadequately treated OSA has been found to be a contributor to many major transportation accidents (55) …”
Section: American Thoracic Society Documentsmentioning
confidence: 99%
“…Shift work disorder is characterized by certain clinically significant disturbances in sleep, fatigue, and/or circadian alignment in shift workers that cannot be attributed to other causes (69). In addition, excessive daytime sleepiness due to shift work, sleep deprivation, sleep disorders, or combinations of these factors is associated with an increased risk of work-related injuries (70)(71)(72)(73). In particular, inadequately treated OSA has been found to be a contributor to many major transportation accidents (55) …”
Section: American Thoracic Society Documentsmentioning
confidence: 99%
“…Year after year, worldwide, this phenomenon is a commonplace for workers, which results in high injury rates for demanding tasks. The injury risk can also be influenced by individuals' characteristics such as social stratification factors including low education, lower socio-occupational category, younger or older age, unhealthy behaviors (smoking, alcohol misuse, obesity, lack of leisure physical and sports activity), altered health status, sleep disorders, mental disorders, and chronic diseases [2][3][4][5][9][10][11][12][13][14][15]. During the last 2 decades research studies have shown that these factors influence the injury risk through physical/mental capacity, knowledge, experience, risk perception, and perceived prevention benefits.…”
Section: Introductionmentioning
confidence: 99%
“…A mechanism behind working hour arrangements and the risk of accidental injuries is suggested to go through sleepiness or fatigue [reviewed in (13)], which are well-known consequences of shift and night work, as well as long work weeks [reviewed in (14-16)]. A key element is sleep, which is determined by two independent biological mechanisms: the circadian rhythm or "body clock", where sleepiness peaks in the early morning, usually between 02:00-06:00 hours, and "sleep pressure", which expresses the amount of fatigue that gradually accumulates during the course of being awake, due to mental and physical activity (17).…”
mentioning
confidence: 99%